New Treatment Opportunities in Phosphatase and Tensin Homolog (PTEN)-Deficient Tumors: Focus on PTEN/Focal Adhesion Kinase Pathway - Alfieri, Roberta; Giovannetti, Elisa; Bonelli, Mara; Cavazzoni, Andrea (Frontiers in Oncology, 2017)
Deep genetic studies revealed that PTEN mutations or loss of expression are not early events in cancer development, but characterize tumor progression and invasion. Loss of PTEN function causes a full activation of the pro-survival PI3K/AKT/mTOR pathway, but the treatment with specific inhibitors of PI3K/AKT/mTOR did not produce the expected results. One of the alternative targets of PTEN is the FAK kinase, mainly involved in the control of cancer cell spread. The connection between PTEN and FAK has been demonstrated in different tumor types, with reduced PTEN activity often correlated with increased expression and phosphorylation of FAK. FAK inhibition may thus represent a promising strategy, and some clinical trials are testing FAK inhibitors alone or combined with other agents in a number of solid tumors. However, only few pre-clinical and clinical data described the effects of the combination of PI3K/AKT/mTOR and FAK inhibitors. Increasing knowledge on the PTEN/FAK connection could confirm PTEN as a good prognostic marker for a combination strategy based on concomitant inhibition of PI3K/AKT and FAK signaling, in advanced metastatic malignancies with altered or reduced PTEN expression.